2023
DOI: 10.1021/acscentsci.3c00572
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Deep Learning for Structure-Based Ligand Design

Alexander S. Powers,
Helen H. Yu,
Patricia Suriana
et al.

Abstract: A pervasive challenge in drug design is determining how to expand a ligand�a small molecule that binds to a target biomolecule�in order to improve various properties of the ligand. Adding single chemical groups, known as fragments, is important for lead optimization tasks, and adding multiple fragments is critical for fragmentbased drug design. We have developed a comprehensive framework that uses machine learning and three-dimensional protein−ligand structures to address this challenge. Our method, FRAME, ite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Aggravatingly, recent work also suggests that many SBDD deep learning models merely memorise the ligands, resulting in poor generalisability and outcomes [8]. In the case of models predicting the binding affinity directly, studies have shown that many of these models consider less of the protein-ligand interaction but more so of quantitative structure analysis relationship (QSAR) of the ligand alone in making their predictions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Aggravatingly, recent work also suggests that many SBDD deep learning models merely memorise the ligands, resulting in poor generalisability and outcomes [8]. In the case of models predicting the binding affinity directly, studies have shown that many of these models consider less of the protein-ligand interaction but more so of quantitative structure analysis relationship (QSAR) of the ligand alone in making their predictions [9].…”
Section: Introductionmentioning
confidence: 99%
“…As a data-driven methodology, its outcomes would be impaired by the limited number of available studies or inconsistent data sets resulting from experimental variations. , Additionally, different peptides may possess distinct working mechanisms that are not directly incorporated into existing peptide databases, further impacting the efficacy of machine learning algorithms . In fact, in nearly all machine-learning scenarios, peptides with higher predicted scores may exhibit poorer biological activity in actual tests. ,, On the other hand, human expertise has been proven helpful in improving peptide performance despite potential biases present within it. , Therefore, effectively leveraging the advantages of machine learning to augment human knowledge holds greater promise for advancing peptide-based drug development.…”
Section: Introductionmentioning
confidence: 99%